Logistics Cost Analysis in Fish Supply Chain in West Sumatra Using Activity-based Costing Method - Iskandar, Yelita Anggiane; Ikhlas, Muhammad Fajar; Hartono, Werdaningtyas Evivani; Afdiyan, Hafidz Al; Mubarak, Alfi (Majalah Ilmiah Bijak, 2024)
Pariaman is a city in West Sumatra with many residents whose livelihoods are in the fisheries sector. Usaha Perikanan Mandiri Muaro Cinto (UPMMC) located in the Pariaman area faces challenges in managing logistics costs. This MSME has not been able to identify the components of the logistics costs of the business they run so business improvement strategies have not been formulated considering that key activities along the supply chain have not been mapped. Therefore, a logistics cost analysis was conducted for the UPMMC fish supply chain using the activity-based costing method. Several actors in the supply chain observed include suppliers, distributors, manufacturers/retailers, and customers. Based on the calculations carried out, it is known that the largest costs are in procurement activities, especially in fishing operations with a proportion of 33.15%. In addition, it is also known that shipping costs have a proportion of 32.93% or equivalent to IDR 2,143 per kg of tuna while packaging costs take a proportion of 19.98% of the total logistics costs.